Effective population size in carp hatcheries of Asom, India - Das, S K (The Indian Journal of Animal Sciences, 2012)
Carp hatcheries in Asom are the major source of fish seeds for aquaculture. Over the years although the state produced a large quantity of fish seeds mostly in the private sector; the state’s market fish production has not increased significantly. Genetic deterioration in the hatchery population may be one of the principal factors affecting the fish production. An attempt was made to study the effective population size of randomly selected hatcheries of the state. The preliminary study revealed that Ne (Effective population size) ranged from 5.23 +2.88 to 16.51+5.56. A significant difference in the estimated effective population size was observed among the different fish species used in both government and private hatcheries. There was, however, no significant difference in the estimated effective population size of different fish species when the ANOVA was tested separately for government and private hatcheries. The study highlights the importance of effective population size in the carp hatcheries to reduce the genetic drift and inbreeding. Through this maiden study an effort was made to advocate proper policy instruments for sustainable development of fish seed industry in the State.